Identification of differential rice cultivars for characterization of rice tungro disease isolates of India - and JASVIR SINGH, C.N. BIJU, F.R. NIAZI (Indian Phytopathology, 2009)
Rice tungro virus isolates from six locations from India were assayed on a newly standardized set of 15 differential rice cultivars. Six distinct strains were identified and characterized on the basis of per cent infection on these differential cultivars.